DISCRETE ELEMENT MODELLING OF CONTRACTIONAL FAULT- PROPAGATION FOLDING ABOVE RIGID BASEMENT FAULT BLOCKS - Finch E.; Hardy S.; Gawthorpe R. (My University, 2003)
Many studies have shown that discrete (blind) faults at depth are commonly linked to more distributed deformation, in particular folding, at higher levels. One category of fault-related folds, forced folds, is common where there is a distinct mechanical contrast between faulted basement and sedimentary cover. Outcrop, numerical and analogue modelling studies indicate that such folds form as upward widening zones of distributed deformation (monoclines) above discrete faults at depth. With increasing displacement the folds are often cut by faults as they propagate upwards into the cover. While the trishear kinematic model of fault-propagation folding appears to approximately represent the geometric development of such structures, comparatively little is known of the mechanical controls on their development.
Keywords: Fault-propagation folding; Forced folds; Modelling; Fault tip